RELASI KIYAI-SANTRI DI PESANTREN MODERN ALKHAIRAAT MANADO - Ahmad Rajafi; Lisa Aisyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2017)
Pesantren ’s distinctive characteristics, is an intelligent cultural product which should be maintained and preserved sustainably. In Manado, Pesantren Alkhairaat becomes an important element in preserving tradi- tions of kepesantrenan (a-la pesantren) which is influenced by Arab tradi- tion. The relationship between kiai (clerics) with their santri (students), as a caretaker-caregiver should be studied, to determine the attempt of those two elements in maintaining pesantren’s unique traditions, as also the patterns of relationship that exist between them. As an Islamic insti- tution in Manado, Pesantren Alkhairaat until recently is still practicing some of typical Islamic traditions that became it’s trademark. Relation- ship between various elements, especially kiai-santri is an important fac- tor for the continuity of these traditions in the future. Moreover, kiai- santri relationship in Pesantren Akhairaat Manado is more likely based on emotional relationships.